The Contribution of the Government and other Stakeholders in enhancing the Socioeconomic Status of the Widows in Kenya - Birech, Jeniffer Kosgey (Advances in Social Sciences Research Journal, 2019)
ABSTRACT Worldwide, the number of widows continue to increase. According to the World Widows Report, there are an estimated 258.5 million widows globally, having increased by 9% between 2010 and 2015. The increase is mainly attributed to conflict and disease. One in seven widows, about 38 million, lives in extreme poverty. The ratio of widows to that of widowers is as high as 4:1. The loss of a spouse precipitates disruption of the family, yet the consequences of losing a spouse is not the same for men and women. In most African communities, widowhood is not only a personal status but also a social one. The widows face social and economic hardships in the area of social participation, decision making and property ownership. Kenya has an estimated 8 million widows and is placed at position 33 in the list of countries in the world that have a harsh environment for the widows. In Nandi county, the female-headed households account for 26.2% of the total households. The existing studies have concentrated on cultural issues such as burial rites. Limited research has been done on opportunities available for the widow to sustain and enhance their livelihood. The role of the government and other stakeholders such as Non-governmental organizations (NGOs), religious organizations and the family, in enhancing the socioeconomic status of the widows have not been exhaustively explored. The paper is guided by three questions; What is the contribution of the Kenyan government and other stakeholders in enhancing the socioeconomic status of the widows? What are the challenges faced by the stakeholders in enhancing the socioeconomic status of the widows? What are the strategies put in place to increase the capacity of the stakeholders? The paper is grounded on Social Exchange Theory and the Theory of Redefinition by William Thomas. Survey Research was utilized. A sample of 250 widows was proportionately distributed across the population to ensure equal representation across Nandi county. Primary data was collected through focussed group discussions, key informants and case histories. The outcome contributes to the already existing body of knowledge on widowhood. It will also create an awareness to the government and other stakeholders on the unique needs of the widows. It will also help identify equity gaps which policy may help close. Therefore, this study will provide information on widows as one of the social groups for the purpose of having the right policies and providing specific strategies on how best to assist them. Key Words: Contributions, Government, Stakeholders, Socioeconomic status, Widows, Kenya. ABSTRACT Worldwide, the number of widows continue to increase. According to the World Widows Report, there are an estimated 258.5 million widows globally, having increased by 9% between 2010 and 2015. The increase is mainly attributed to conflict and disease. One in seven widows, about 38 million, lives in extreme poverty. The ratio of widows to that of widowers is as high as 4:1. The loss of a spouse precipitates disruption of the family, yet the consequences of losing a spouse is not the same for men and women. In most African communities, widowhood is not only a personal status but also a social one. The widows face social and economic hardships in the area of social participation, decision making and property ownership. Kenya has an estimated 8 million widows and is placed at position 33 in the list of countries in the world that have a harsh environment for the widows. In Nandi county, the female-headed households account for 26.2% of the total households. The existing studies have concentrated on cultural issues such as burial rites. Limited research has been done on opportunities available for the widow to sustain and enhance their livelihood. The role of the government and other stakeholders such as Non-governmental organizations (NGOs), religious organizations and the family, in enhancing the socioeconomic status of the widows have not been exhaustively explored. The paper is guided by three questions; What is the contribution of the Kenyan government and other stakeholders in enhancing the socioeconomic status of the widows? What are the challenges faced by the stakeholders in enhancing the socioeconomic status of the widows? What are the strategies put in place to increase the capacity of the stakeholders? The paper is grounded on Social Exchange Theory and the Theory of Redefinition by William Thomas. Survey Research was utilized. A sample of 250 widows was proportionately distributed across the population to ensure equal representation across Nandi county. Primary data was collected through focussed group discussions, key informants and case histories. The outcome contributes to the already existing body of knowledge on widowhood. It will also create an awareness to the government and other stakeholders on the unique needs of the widows. It will also help identify equity gaps which policy may help close. Therefore, this study will provide information on widows as one of the social groups for the purpose of having the right policies and providing specific strategies on how best to assist them. Key Words: Contributions, Government, Stakeholders, Socioeconomic status, Widows, Kenya. ABSTRACT Worldwide, the number of widows continue to increase. According to the World Widows Report, there are an estimated 258.5 million widows globally, having increased by 9% between 2010 and 2015. The increase is mainly attributed to conflict and disease. One in seven widows, about 38 million, lives in extreme poverty. The ratio of widows to that of widowers is as high as 4:1. The loss of a spouse precipitates disruption of the family, yet the consequences of losing a spouse is not the same for men and women. In most African communities, widowhood is not only a personal status but also a social one. The widows face social and economic hardships in the area of social participation, decision making and property ownership. Kenya has an estimated 8 million widows and is placed at position 33 in the list of countries in the world that have a harsh environment for the widows. In Nandi county, the female-headed households account for 26.2% of the total households. The existing studies have concentrated on cultural issues such as burial rites. Limited research has been done on opportunities available for the widow to sustain and enhance their livelihood. The role of the government and other stakeholders such as Non-governmental organizations (NGOs), religious organizations and the family, in enhancing the socioeconomic status of the widows have not been exhaustively explored. The paper is guided by three questions; What is the contribution of the Kenyan government and other stakeholders in enhancing the socioeconomic status of the widows? What are the challenges faced by the stakeholders in enhancing the socioeconomic status of the widows? What are the strategies put in place to increase the capacity of the stakeholders? The paper is grounded on Social Exchange Theory and the Theory of Redefinition by William Thomas. Survey Research was utilized. A sample of 250 widows was proportionately distributed across the population to ensure equal representation across Nandi county. Primary data was collected through focussed group discussions, key informants and case histories. The outcome contributes to the already existing body of knowledge on widowhood. It will also create an awareness to the government and other stakeholders on the unique needs of the widows. It will also help identify equity gaps which policy may help close. Therefore, this study will provide information on widows as one of the social groups for the purpose of having the right policies and providing specific strategies on how best to assist them. Key Words: Contributions, Government, Stakeholders, Socioeconomic status, Widows, Kenya. ABSTRACT Worldwide, the number of widows continue to increase. According to the World Widows Report, there are an estimated 258.5 million widows globally, having increased by 9% between 2010 and 2015. The increase is mainly attributed to conflict and disease. One in seven widows, about 38 million, lives in extreme poverty. The ratio of widows to that of widowers is as high as 4:1. The loss of a spouse precipitates disruption of the family, yet the consequences of losing a spouse is not the same for men and women. In most African communities, widowhood is not only a personal status but also a social one. The widows face social and economic hardships in the area of social participation, decision making and property ownership. Kenya has an estimated 8 million widows and is placed at position 33 in the list of countries in the world that have a harsh environment for the widows. In Nandi county, the female-headed households account for 26.2% of the total households. The existing studies have concentrated on cultural issues such as burial rites. Limited research has been done on opportunities available for the widow to sustain and enhance their livelihood. The role of the government and other stakeholders such as Non-governmental organizations (NGOs), religious organizations and the family, in enhancing the socioeconomic status of the widows have not been exhaustively explored. The paper is guided by three questions; What is the contribution of the Kenyan government and other stakeholders in enhancing the socioeconomic status of the widows? What are the challenges faced by the stakeholders in enhancing the socioeconomic status of the widows? What are the strategies put in place to increase the capacity of the stakeholders? The paper is grounded on Social Exchange Theory and the Theory of Redefinition by William Thomas. Survey Research was utilized. A sample of 250 widows was proportionately distributed across the population to ensure equal representation across Nandi county. Primary data was collected through focussed group discussions, key informants and case histories. The outcome contributes to the already existing body of knowledge on widowhood. It will also create an awareness to the government and other stakeholders on the unique needs of the widows. It will also help identify equity gaps which policy may help close. Therefore, this study will provide information on widows as one of the social groups for the purpose of having the right policies and providing specific strategies on how best to assist them. Key Words: Contributions, Government, Stakeholders, Socioeconomic status, Widows, Kenya.v